2019
DOI: 10.1021/acsami.9b13657
|View full text |Cite
|
Sign up to set email alerts
|

Design Superior Alkaline Hydrogen Evolution Electrocatalyst by Engineering Dual Active Sites for Water Dissociation and Hydrogen Desorption

Abstract: In alkaline media, the water-dissociation-related Volmer process always suppresses the hydrogen formation/ desorption process, which makes it challenging to develop non-noble-metal alkaline electrocatalysts with excellent catalytic activity. Here, we proposed a two-pronged strategy to simultaneously promote the kinetic process of both water dissociation and hydrogen desorption with the Co-doped WO 2 /amorphous Co x W hybrid electrocatalyst. Impressively, the optimized hybrid exhibits an outstanding hydrogen ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…We obtained exchange current density 38 by the combination of the simplified Butler−Volmer equation and eq 2 (2) where R is the ideal gas constant, α is the transfer coefficient, F is the Faraday constant, n is the number of electrons transferred, j 0 is the exchange current density, and j is the kinetic current density. The Tafel slope 39 was obtained from the polarization curve using the Tafel equation3 (3) where η is overpotential, a is the intercept, b is the Tafel slope, and j is the current density.…”
Section: Preparation Of Cb[8]-[ptcl 6 ]mentioning
confidence: 99%
“…We obtained exchange current density 38 by the combination of the simplified Butler−Volmer equation and eq 2 (2) where R is the ideal gas constant, α is the transfer coefficient, F is the Faraday constant, n is the number of electrons transferred, j 0 is the exchange current density, and j is the kinetic current density. The Tafel slope 39 was obtained from the polarization curve using the Tafel equation3 (3) where η is overpotential, a is the intercept, b is the Tafel slope, and j is the current density.…”
Section: Preparation Of Cb[8]-[ptcl 6 ]mentioning
confidence: 99%
“…As shown in Figure 3a and 3b, after removing the Co 3 W alloys, the overpotential at current density of 10 mA cm −2 and Tafel slope of it increase to 90 mV and 114.43 mV dec −1 , respectively, which means Co 3 W alloys play an important role in accelerating the HER kinetic process. Density functional theory (DFT) calculation in previous report has shown that cobalt tungsten alloy has a water dissociation energy barrier of 0.46 eV, closing to 0.44 eV of Pt (110), which could effectively accelerate the water dissociation process of HER in alkaline solution [33] . As widely accepted, Tafel slopes of 120, 40 and 30 mV dec −1 are corresponding to the Volmer, Heyrovsky and Tafel determining rate steps, respectively [34] .…”
Section: Resultsmentioning
confidence: 97%
“…The catalytic activity thereby can be remarkably promoted by effectively integrating the multiple advantages of each component. 33 A novel Ni(OH) 2 /MoS 2 hybrid was developed as active electrocatalysts for HER catalysis in an alkaline solution. 171 The Ni(OH) 2 /MoS 2 electrocatalyst exhibited enhanced electrocatalytic activity with an onset overpotential of 20 mV, and a Tafel slope of 60 mV dec −1 .…”
Section: Interface Engineering Strategiesmentioning
confidence: 97%
“…This phenomenon is perceived as synergistic effect. , For example, different components exhibit specific activity for different elementary steps of reactions. The catalytic activity thereby can be remarkably promoted by effectively integrating the multiple advantages of each component …”
Section: Interface Engineering Strategiesmentioning
confidence: 99%
See 1 more Smart Citation